Ensuring Peace in Society: An Islamic Perspective. - Mahmudul Hassan (al-Afkar, Journal For Islamic Studies, 2023)
The paper attempts to find out the problems against social peace and development, and sheds light on Islamic directions towards ensuring peace in the society. The peace and stability of a society- at most- depend on fulfilling the rights of social members, and removing all types of violations from that society. Cordial relationship among the dwellers also plays a vital role to stable the peace in the society. Islam, therefore, has declared all civil rights of human kinds such as the rights of food, cloth, habitation, education, treatment, social security, freedom of thought and religion etc., and has strongly prohibited all sorts of offenses like killing, stealing, doing injustice, deceiving, teasing, telling a lie, backbiting, slandering, plotting, envying, spying, suspecting, looking into the secret matters of others, committing social discriminations in the society, and so on. For the stability of peace in a society, Islam paid attention to the cordial relationship between the social members and enjoined its followers to ensure philanthropic activities in the society as helping, visiting, exchanging gifts, consoling, paying debts to the needy, healing the poor sick, special care for the aged, disabled and widow, and forgiving the mistakes of social inhabitants.